Comparative in vitro antioxidant analysis of leaf, stem and root extracts of Plumbago zeylanica L. (Plumbaginaceae) - Sangeetha, Girija; Raj, Neethu (Current Botany, 2025)
Medicinal plants have become increasingly popular in modern life because of their numerous beneficial uses in nutrition, healthcare, medication and cosmetics. One such medicinally important plant is Plumbago zeylanica L. which grows in all districts of Kerala, belonging to the family Plumbaginaceae and its Sanskrit name is “Chitrak”. The leaves and roots of the plant contain an alkaloid called Plumbagin. The root yield pigments like3, 3- biplumbagin, 3-chloroplumbagin, binaphthoquinone, droserone, isozeylanone, elliptinone, and zeylanone. The current investigation concentrated on the preliminary evaluation of phytochemical and comparative in vitro antioxidant analysis of leaf, stem and root of P. zeylanica. Screening of phytochemicals showed the presence of various secondary metabolites like alkaloids, glycosides, terpenoids, steroids, flavonoids, phenols and tannins which were present in the root methanolic extract than that of the stem and leaf extracts. The comparative free radical scavenging activities were assessed using a variety of assays, including DPPH, superoxide anion scavenging and nitric oxide scavenging. In the DPPH assay, maximum scavenging activity of the root methanolic extract was observed to be 94.24±1.76% whereas the methanolic leaf and stem extract were found to be 92.65±1.08% and 82.45±0.89% respectively at 200 μg mL-1 concentration. As compared to the IC50 values of the standard drug ascorbic acid, the root methanolic extract showed a lower IC50 value. The lower IC50 value indicates higher free radical scavenging activity. In the superoxide anion scavenging assay, maximum activity was found to be 83.23±2.12% at 200 μg mL-1 concentration of methanolic root extract and the IC50 values exhibited by root methanol extract (39.38±1.03 μg mL-1) were comparatively less than that of standard drug ascorbic acid (48.89±1.67 μg mL-1). In the nitric oxide scavenging assay, the root methanolic extract showed the highest capacity (79.23±2.11%) to decrease the synthesis of nitrite ions than that of leaf and stem extracts. The IC50 value exhibited by root methanol extract (42.17±2.42 μg mL-1) was approximately closer to that of standard drug ascorbic acid (39.38±1.03 μg mL-1). The outcome indicates that P. zeylanica root extract has the highest potential for antioxidants than compared to leaf and stem extracts. The secondary metabolites contained in roots might be contributing to this maximum antioxidant activity and it may be an excellent source of natural antioxidant.